The long-term effects of adverse childhood experiences on adult health and behaviors: mediating role of socioeconomic inequality - Yanling Shu; Zheng Zhang; Hengyu Wang; Chunling Wang; Linfei Dou; Wenhua Wang; Lei Zhang; Jianing Bi; Mingyang Wu (BMC Public Health)
Abstract Background Despite extensive research into the health effects of adverse childhood experiences (ACEs), there remains a need for nationally representative data to assess the associations between ACEs and both adult health and behaviors, focusing on the mediating role of socioeconomic inequality. Method Using data from the 2019–2022 Behavioral Risk Factor Surveillance System (BRFSS) (N = 249,186 adults), ACE exposure was categorized into five groups (0, 1, 2, 3, and 4 or more ACEs). Socioeconomic inequality was assessed based on income levels. Binary logistic regression was employed to quantify the associations of ACEs/socioeconomic inequality with adult health and behaviors. Mediation models were used to evaluate the mediating effect of socioeconomic inequality on the relationships of continuous ACE scores with adult health and behaviors. Results Each unit increase in ACE score was associated with a 4–34% increase in the odds of adverse health outcomes or unhealthy behaviors. Compared to participants with no ACE exposure, those with ≥ 4 ACEs exhibited a higher likelihood of experiencing asthma, arthritis, cancer, cardiovascular disease (CVD), chronic obstructive pulmonary disease (COPD), diabetes, disability, depression, more days of poor physical and mental health, and engagement in drinking, smoking and high-risk HIV behavior, with odds ratios ranging from 1.26 (95% CI: 1.22–1.31) for diabetes to 4.87 (95% CI: 4.72–5.02) for depression. Socioeconomic inequality mediated more than 5% of associations between ACE scores and diabetes, disability, COPD, and CVD. Conclusions This study reveals a broad spectrum of negative health impacts associated with ACE exposure, with socioeconomic inequality demonstrating a significant mediating effect on these associations. The findings emphasize the need for public health interventions targeting both ACEs and socioeconomic inequality to alleviate the burden of chronic diseases and improve adult health conditions.